Experimental study of fuel evaporation characteristics. (1st April 2016) - Yan, Yingwen; Liu, Yunpeng; Wang, Yajun; Li, Jinghua; Cai, Wenxiang
Abstract: Fuel evaporation characteristics are very important for the design of combustors. To quantitatively measure the fuel evaporation ratio of jet fuel in air cross flow, optical and physical measurement methods are proposed separately. The optical measurement method combines a high-speed camera and image-processing technologies, where as the physical measurement method applies the centrifugal force of a cyclone separator. The fuel evaporation ratio at different inlet conditions and different measurement cross-sections is analyzed separately for jet fuel in air cross flow. Finally, the experimental results of the physical method are compared with those of the optical method. The experimental results show that (1) the results of the optical measurement method are in good agreement with those of the physical measurement method, and these two methods can be used to quantitatively measure the fuel evaporation ratio at individual test cross-sections; (2) when other inlet parameters are the same, the fuel evaporation ratio at the test cross-section gradually increases with increasing inlet air Weber number; (3) when other inlet parameters are the same, the fuel evaporation ratio at the test cross-section gradually decreases with increasing momentum ratio; and (4) when inlet parameters are the same, the fuel evaporation ratio at the test cross-section increases sharply with increasing distance between the test cross-section and nozzle.